Religious Moderation in Islamic Law and Its Educational Implementation: A Normative and Pedagogical Analysis - Yossef Yuda; Akhiyen Nuardi; Nurhadi Ahmad; Elgusri Elgusri; Syaifullah Syaifullah; Riki Saputra (Journal of General Education and Humanities, 2026)
This study addresses the growing challenges of religious radicalism and exclusivism in the public sphere by reconstructing the concept of wasathiyyah (moderation) within Islamic law and its application in education. Employing a qualitative literature review with a legal-normative approach, this research analyses classical and contemporary Islamic legal texts, including the Qur'an, Sunnah, fiqh principles, and Maqasid al-Shariah, using descriptive-analytical and content analysis methods. The findings reveal that Islamic law fundamentally upholds justice ('adl) and balance (i'tidal) as core pillars of moderation. Moderation is not a dilution of faith but a return to the essence of Sharia, rejecting both textualist extremism and liberal overreach. In educational contexts, moderation is applied through an inclusive curriculum, dialogic learning methods, and an institutional culture that fosters tolerance (tasamuh). This research suggests that integrating Islamic legal principles into pedagogy can reduce religion-based conflicts and foster sustainable social harmony. The study is limited to theoretical analysis and suggests future empirical research on implementing moderation models in diverse educational settings. The contribution lies in providing a theoretical framework for developing Islamic education that produces graduates who are intellectually and spiritually intelligent.